Quality of life after gastric sleeve and gastric bypass for morbid obesity - Ramada Faria, Gil Filipe (Porto Biomed J, 2017)
HIGHLIGHTS: Quality-of-life measures improve as early as 3 months after bariatric surgery. There is wide variability in reporting that renders direct comparisons difficult. The available comparisons between RYGB and sleeve gastrectomy could not detect any difference. Improvement in PRO measures might be related to weight loss. Larger and better designed studies are required to achieve discrimination in PRO measures. BACKGROUND: Obesity is associated with reduced quality-of-life (QoL), which generally improves after bariatric surgery. The differential effect of each type of surgery (gastric sleeve [SG] and gastric bypass [RYGB]) on QoL is not yet fully understood. OBJECTIVES: To understand which of these surgeries offers greatest improvement in QoL and patient satisfaction. METHODS: Systematic literature search on Pubmed in July 2014. Relevant articles were selected in a step-wise approach. The 2482 titles were scanned for relevance and 191 were selected for abstract reviewing; and 88 papers were selected for full text analysis. RESULTS: Only 5 papers compared the 2 techniques and only 17 more had retrievable data either on SG or RYGB. The reports were very heterogeneous, preventing a direct comparison of patient reported outcomes (PRO) among studies. Improved results have been reported as early has 3 months and SF-36 scores were improved in all domains in medium to long-term. The question remains whether the improvement in QoL is related to the weight loss and which factors are associated with improved patients' perceptions. CONCLUSIONS: There is wide heterogeneity in the reporting of PRO measures after bariatric surgery, but data is consistent with a significant improvement after both surgeries. Larger and better-designed studies are required to understand if there are significant differences in the quality of life after SG or RYGB.